2013
DOI: 10.1021/la403457c
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Self-Assembly Dependent Spatial Distribution of Small Molecules in a Cellular Environment

Abstract: Self-assembly of small molecules, as a more common phenomenon than one previously thought, can be either beneficial or detrimental to cells. Despite its profound biological implications, how the self-assembly of small molecules behave in cellular environment is largely unknown and barely explored. This work studies four fluorescent molecules that consist of the same peptidic backbone (e.g., Phe-Phe-Lys) and enzyme trigger (e.g., a phosphotyrosine residue), but bear different fluorophores on the side chain of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 47 publications
0
37
0
Order By: Relevance
“…However, the self-assembling tendencies and the distribution of the self-assembled fibers in the cellular environment can be heavily influenced by the nature of the fluorophore, and can also induce cytotoxicity in some cases. Thus, extreme care must be exercised in designing the fluorophore precursors to achieve the desired imaging objectives [84]. …”
Section: Peptide-peptide Interaction Driven Self-assemblymentioning
confidence: 99%
“…However, the self-assembling tendencies and the distribution of the self-assembled fibers in the cellular environment can be heavily influenced by the nature of the fluorophore, and can also induce cytotoxicity in some cases. Thus, extreme care must be exercised in designing the fluorophore precursors to achieve the desired imaging objectives [84]. …”
Section: Peptide-peptide Interaction Driven Self-assemblymentioning
confidence: 99%
“…Notably, this small molecule exhibited remarkable cytotoxicity to several cancer cell lines while showed low cytotoxicity to normal cells due to the fact that cancer cells secrete excessive amount of MMP-7. Based on the report of the intracellular EISA of L-peptide derivative (Nap-FFK p Y),[119, 305, 306] Gao et al reported the use of Nap-FFK p Y to co-assemble with indocyanine green (ICG) for in vivo cancer theranostics. The formation of ICG-doped nanofibers not only enhanced the tumor uptake of ICG (by 25-fold compared with free ICG), but also largely extended the retention time of ICG in tumor site, resulting in complete and precise tumor elimination by laser ablation (Figure 16C).…”
Section: Applications Of Supramolecular Biofunctional Materialsmentioning
confidence: 99%
“…DBD). [52] Upon enzymatic dephosphorylation (Fig. 7a), these precursors transform to their corresponding hydrogelators and exhibit higher contrast than background for imaging.…”
Section: Spatiotemporal Control Of Nanoscale Assemblies and The Bimentioning
confidence: 99%
“…Fluorescent confocal images of the HeLa cells incubated with 500 µM of (c) 6a , (d) 7a , (e) 8a , and (f) 9a for 30 min. [52] (Print with the permission from © 2013 American Chemical Society)…”
Section: Figurementioning
confidence: 99%